Reconfiguring Embodiment: Online Experimentation and Embodied Practices of Self - Tiidenberg, Katrin; Ungbha Korn, Jenny; Wheaton, Hilary; Moody, Kyle (AoIR Selected Papers of Internet Research, 2013)
Abstract This panel consists of the following papers: “Anonymity in Chatroulette: Embodied Practices Within Online Impression Management”; “The Embodied Mods: How Modders in Virtual Spaces Embody Practices of Self Through Virtual Community Creation and Values”; “There and back again - a Self-Shooters Tale: reconfiguring embodiment via selfies”; “Internet Dating: Technologies Appropriation of the Body for Targeted Relationship Initiation”. Research covers a variety of platforms – Chatroulette, tumblr.com; Skyrim Nexus; adultfriendfinder.com, and redhotpie.com.au. Authors have conducted visual narrative analysis; textual analysis of data pulled from a blended ethnographic study; autoethnographic analysis of active participation-observation, and discourse analysis. Advocates and critics alike have long claimed “virtuality” as a space of identity play, construction, and tourism, either a (safe) space of exploration (Alvesson et al, 2008; Bargh & McKenna, 2004; Bargh, McKenna & Fitzsimons, 2002; Baym, 2000; boyd, 2006, 2007; boyd & Heer, 2006; boyd & Ellison, 2007; Daneback, 2006; Hardey, 2002; Joinson, 2008; Ross, 2005; Whitty, 2003) or zone of dysfunction and deceit (Brym & Lenton, 2001; Gibbs, Ellison & Heino, 2006; Toma, Hancock & Ellison, 2008). How do we navigate the space of intermixing, the borderlands of identities as the distinctions between “virtual” and “real” continues to blur (Orgad, 2009; Baym & Markham, 2009)? As online users blend digital and physical practices, the meanings attached to the self and the body are reconfigured, ranging from discovery to obfuscation. In late-modernity, the body and the self have become sites of interaction, appropriation, and reappropriation (Giddens, 1991, p.218). Some users who experiment online are impelled to transition bodily, while others return to normative expression. Self-evaluation and playacting as ways of testing the boundaries of social roles may lead to reconfiguring of habits, customs, and representations. In this context, the increased participation in media content creation and the consequently blurred role of “gatekeeper” (see Jenkins, 2006; Deuze, 2007) is another factor in the reconfiguration of embodiment. For example, as a result of online experimentation, individuals may select a new hobby, career, or professional identity, and thus become a member of a physical community of practice, which would again minimize the distance between online and offline selves. Through produsage (Burns, 2006) practices, the virtual self is implemented into modified, cultural content (cf. ludic practices and identity, Aarseth, 1998). Some virtual worlds and online communities inspire a material turn, while others keep users bound within the “magic circle” of the digital imaginative. Our work will examine the embodied identity projects in the borderlands of material and mediated self across a range of platforms and practices, including appropriation of users’ bodies and sexualities for the purpose of internet dating, modding as a form of cultural expression and community engagement, impression building in Chatroulette, and self-shooting as a technology of self. Our panel explores how online and offline practices reconfigure the meaning of the embodied self for ourselves and those around us through innovative applications of qualitative methodologies. Specifically, this panel’s authors conduct visual narrative analysis of images, captions, ethnographic field notes, and interviews of a self-shooters’ community on tumblr.com; textual analysis of data pulled from a blended internet ethnographic study including field research, interviews, and participant observation on the popular mod distribution and news channels Steam Workshop and Skyrim Nexus; autoethnographic analysis of active participation-observation in Chatroulette (Chatroulette.com), and discourse analysis of AdultFriendFinder (adultfriendfinder.com) and RedHotPie (redhotpie.com.au). Through our combined research, this panel demonstrates the relationships between self and community, particularly within the blurred role of creator and consumer of game content while modding. It inspects how interactions or representations in internet dating sites can be incompatible with those in the actual world, not due to intended deceit, but because of a failure to recognize how the internet may allow the true self to be more easily expressed. This panel also offers the first academic examination of Chatroulette as an ethnographic site of analysis and demonstrates the importance of the socially-enacted, embodied self in online encounters that center upon quick evaluations of the body. In addition, it explores how we can construct a sexier, more lovable “reflexive body” as a result of aesthetic self-stylization and critical self-awareness in self-shooting and body-blogging. Via analyses of the aformentioned virtual-material practices, this panel illuminates contemporary Internet research phenomena of modding, Chatroulette, self-shooting, and dating. This panel extends the discussion of embodied self-identity online and contributes to new knowledge on the material return of the body in the realm of the virtual. References: Aarseth, E. (1997). Cybertext: Perspectives on ergodic literature. Baltimore: Johns Hopkins University Press. Alvesson, M., Lee Ashcraft, K., & Thomas, R. (2008). Identity Matters: Reflections on the Construction of Identity Scholarship in Organization Studies. Organization, 15(1), 5–28. doi:10.1177/1350508407084426 Bargh, J. a, & McKenna, K. Y. a. (2004). The internet and social life. Annual review of psychology, 55, 573–90. doi:10.1146/annurev.psych.55.090902.141922 Bargh, J. A., Mckenna, K. Y. A., & Fitzsimons, G. M. (2002). Can You See the Real Me ? Activation and Expression of the “ True Self ” on the Internet. Journal of Social Issues 58(1), 33–48. Baym, N. K. (2000). Tune In, Log On: Soaps, Fandom, and Online Community. Thousand Oaks, Sage. Baym, N. K., Markham, A. N. (2009). Introduction. Making Smart Choices on Shifting Ground. In Markham, A. N., Baym, N. K. (eds.) Internet Inquiry, conversations about method. Thousand Oaks: Sage. boyd, d. (2007). ‘Why Youth (Heart) Social Network Sites: The Role of Networked Publics in Teenage Social Life.’ In Buckingham, D. (Ed.). MacArthur Foundation Series on Digital Learning – Youth, Identity, and Digital Media Volume (pp. 119-142). Cambridge, MA: MIT Press. boyd, d. (2007). ‘Social Network Sites: Public, Private, or What?’ Knowledge Tree, 13. boyd, d. and Heer, J. (2006). ‘Profiles as Conversation: Networked Identity Performance on Friendster.’ Proceedings of the 39th Hawaii International Conference on System Sciences – 2006. Boyd, D. M., & Ellison, N. B. (2007). Social Network Sites: Definition, History, and Scholarship. Journal of Computer-Mediated Communication, 13(1), 210–230. doi:10.1111/j.1083-6101.2007.00393. Brym, R. J., & Lenton, R. L. (2001). Love online: A report on digital dating in Canada. Retrieved from: http://projects.chass.utoronto.ca/brym/loveonline.pdf. Bruns, Axel (2006) Towards Produsage: Futures for User-Led Content Production. In Sudweeks, F., Hrachovec, H. & Ess, C. (Eds.) Proceedings Cultural Attitudes towards Communication and Technology, pp. 275-284, Tartu, Estonia. Daneback, K. (2006). Love and sexuality on the internet. Landscape. Deuze, M. (2007). Media work. Cambridge: Polity Press. Gibbs, J. L., Ellison, N. B., & Heino, R. D. (2006). Self-presentation in online personals: The role of anticipated future interaction, self- disclosure, and perceived success in Internet dating. Communication Research, 33, 1-26. Giddens A. (2010 [1991]). Modernity and Self Identity, Self and Society in the Late Modern Age. Cambridge: Polity Press. Hardey, M. (2002). Life beyond the screen : embodiment and identity through the internet. The Editorial Board of The Sociological Review (46), 570 – 585. Jenkins, H. (2006). Convergence culture: Where old and new media collide. New York: New York University Press. Joinson, A. N. (2008). “ Looking at ”, “ Looking up ” or “ Keeping up with ” People ? Motives and Uses of Facebook. CHI 2008, April 5–10, 2008, Florence, Italy. Orgad, S. (2009). Question Two: How Can Researchers Make Sense of The Issues Involved in Collecting and Interpreting Online and Offline Data? In Markham A. M, Baym N. K. (Eds.) Internet Inquiry, conversations about method. Thousand Oaks: Sage. Ross, M. W. (2005). ‘Typing, doing and being: sexuality and the Internet.’ Journal of Sex Research, 42: 342-52. Toma, C.L; Hancock, J; Ellison, N. (2008). Separating Fact From Fiction: An Examination of Deceptive Self-Presentation in Online Dating Profiles. Personality and Social Psychology Bulletin. 34, 8: 1023-1036. DOI: 10.1177/01461672083180 Whitty, M. T. (2003). ‘Pushing the Wrong Buttons: Men’s and Women’s Attitudes toward Online and Offline Infidelity.’ Cyberpsychology and Behavior, 6: 569-579.